Cytotoxicity, Intestinal Transport, and Bioavailability of Dispersible Iron and Zinc Supplements - Kim, Hyeon-Jin; Bae, Song-Hwa; Kim, Hyoung-Jun; Kim, Kyoung-Min; Song, Jae Ho; Go, Mi-Ran; Yu, Jin; Oh, Jae-Min; Choi, Soo-Jin (Frontiers in Microbiology, 2017)
Iron or zinc deficiency is one of the most important nutritional disorders which causes health problem. However, food fortification with minerals often induces unacceptable organoleptic changes during preparation process and storage, has low bioavailability and solubility, and is expensive. Nanotechnology surface modification to obtain novel characteristics can be a useful tool to overcome these problems. In this study, the efficacy and potential toxicity of dispersible Fe or Zn supplement coated in dextrin and glycerides (SunActive FeTM and SunActive ZnTM) were evaluated in terms of cytotoxicity, intestinal transport, and bioavailability, as compared with each counterpart without coating, ferric pyrophosphate (FePP) and zinc oxide (ZnO) nanoparticles (NPs), respectively. The results demonstrate that the cytotoxicity of FePP was not significantly affected by surface modification (SunActive FeTM), while SunActive ZnTM was more cytotoxic than ZnO-NPs. Cellular uptake and intestinal transport efficiency of SunActive FeTM were significantly higher than those of its counterpart material, which was in good agreement with enhanced oral absorption efficacy after a single-dose oral administration to rats. These results seem to be related to dissolution, particle dispersibility, and coating stability of materials depending on suspending media. Both SunActiveTM products and their counterpart materials were determined to be primarily transported by microfold (M) cells through the intestinal epithelium. It was, therefore, concluded that surface modification of food fortification will be a useful strategy to enhance oral absorption efficiency at safe levels.